Investigations into the structure of La3Ni2−xFexO7±δ - Evgeny Alexandrovich Kiselev; Piotr Gaczynski; Götz Eckold; Armin Feldhoff; Klaus-Dieter Becker; Vladimir Alexandrovich Cherepanov (Chimica Techno Acta)
The room-temperature (RT) 57Fe Mössbauer spectra of the La3Ni2−xFexO7±δ oxide solid solutions of Ruddlesden-Popper-type (x = 0.05, 0.10) reveal two doublets for Fe3+ ions in octahedral coordination by oxygen. The existence of two inequivalent sites for Fe at RT is at variance with the space groups Fmmm and Cmcm (Amam) which have been reported for La3Ni2O7±δ. This unexpected finding is discussed in connection with Patterson analyses and Rietveld refinements of powder XRD data for x = 0, 0.05, and 0.10. Alternative structural models have been proposed which can explain the spectroscopic findings and which are compatible with the results from X-ray diffraction.